Pengaruh faktor personality disposisional dan kognitif situasional terhadap niat penggunaan internet - WILLY, Abdillah ([Yogyakarta] : Universitas Gadjah Mada, 2008)
Willy Abdillah : Manajemen : Universitas Bengkulu : Prof. Dr. Jogiyanto Hartono, MBA., Akt. : 29 Oktober 2008 The objective of this research is to investigate the effect of dispositional personality and situational cognitive factors on the intention to use internet. Personality factors are measured by five variables openness to experience, conscientiousness, extraversion, agreeableness and neuroticism . Meanwhile, situational cognitive factors are measured by perceived ease of use, perceived usefulness and self-efficacy. Survey was conducted to 350 students of Economic Faculty of university of Bengkulu, include extension and Magister Management students program. This research use non-probability sampling procedure which purposive-judgment method. Primary data were gathered using closedquestion form questionnaire. Hypotheses testing were conducted using Partial Least Square with software SmartPLS version 2.0. Result showed that only openness to experience from personality factors was significantly affected on intention to use internet. Meanwhile, perceived usefulness and self-efficacy were positively affected from situational cognitive factors. For comparison testing showed that situational cognitive factors were better predictor than personality factors on the intention to use internet. These results imply theoretically to support for information technology acceptance and adoption theory which dominantly based on perceptual cognitive as robust theory. Practically these results offer strategic information for higher education managers how to manage common problems of information system resistance. Moreover, resistance wouldn’t be come as long as informatio n technology offer benefit for users and there is a set of education, persuasion and training programs.